Targeted phenotypic screening in plasmodium falciparum and toxoplasma gondii reveals novel modes of action of medicines for malaria venture malaria box molecules - Subramanian, Gowtham (mSphere, 2018)
The Malaria Box collection includes 400 chemically diverse small molecules with documented potency against malaria parasite growth, but the underlying modes of action are largely unknown. Using complementary phenotypic screens against Plasmodium falciparum and Toxoplasma gondii, we report phenotype-specific hits based on inhibition of overall parasite growth, apicoplast segregation, and egress or host invasion, providing hitherto unavailable insights into the possible mechanisms affected. First, the Malaria Box library was screened against tachyzoite stage T. gondii and the half-maximal effective concentrations (EC50s) of molecules showing ≥80% growth inhibition at 10 µM were determined. Comparison of the EC50s for T. gondii and P. falciparum identified a subset of 24 molecules with nanomolar potency against both parasites. Thirty molecules that failed to induce acute growth inhibition in T. gondii tachyzoites in a 2-day assay caused delayed parasite death upon extended exposure, with at least three molecules interfering with apicoplast segregation during daughter cell formation. Using flow cytometry and microscopy-based examinations, we prioritized 26 molecules with the potential to inhibit host cell egress/invasion during asexual developmental stages of P. falciparum. None of the inhibitors affected digestive vacuole integrity, ruling out a mechanism mediated by broadly specific protease inhibitor activity. Interestingly, five of the plasmodial egress inhibitors inhibited ionophore-induced egress of T. gondii tachyzoites. These findings highlight the advantage of comparative and targeted phenotypic screens in related species as a means to identify lead molecules with a conserved mode of action. Further work on target identification and mechanism analysis will facilitate the development of antiparasitic compounds with cross-species efficacy.

Targeted phenotypic screening in plasmodium falciparum and toxoplasma gondii reveals novel modes of action of medicines for malaria venture malaria box molecules (vol 3, e00534-17, 2018) - Subramanian, Gowtham; Belekar, Meenakshi A.; Shukla, Anurag; Tong, Jie Xin; Sinha, Ameya; Chu, Trang T. T.; Kulkarni, Akshay S.; Preiser, Peter R.; Reddy, D. Srinivasa; Tan, Kevin S. W.; Shanmugam, Dhanasekaran; Chandramohanadas, Rajesh (MSphere, 2019)